2013
DOI: 10.1039/c2ra22299j
|View full text |Cite
|
Sign up to set email alerts
|

Potential therapeutic and diagnostic applications of one-step in situ biosynthesized gold nanoconjugates (2-in-1 system) in cancer treatment

Abstract: Potential therapeutic and diagnostic applications of one-step in situ biosynthesized gold nanoconjugates (2in-1 system) in cancer treatment3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 56 publications
1
36
0
Order By: Relevance
“…Green synthesis is a non-toxic method due to very less or non-consumption of hazardous materials on the surface of nanomaterials. Biosynthesized nanoparticles by green synthesis are normally biocompatible and have more biomedical applications [6,7]. Furthermore, the phytochemical constituents of Azadirachta indica (A. indica) (neem) can block cancer growth, and they have strong reducing properties [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Green synthesis is a non-toxic method due to very less or non-consumption of hazardous materials on the surface of nanomaterials. Biosynthesized nanoparticles by green synthesis are normally biocompatible and have more biomedical applications [6,7]. Furthermore, the phytochemical constituents of Azadirachta indica (A. indica) (neem) can block cancer growth, and they have strong reducing properties [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Daizy et al [21] reported that Cassia fistula stem bark mediated Au-NPs are better hypoglycemic agents in the treatment of diabetes mellitus and its associated complications. Mukherjee et al [22] proposed that green synthesized gold nanobioconjugates using Olax Scandens leaf (Au-NPs-OX) could be used as alternative diagnostic and therapeutic approaches for cancer diseases. Kumar et al [23] reported that the physicochemical properties, biostability and blood compatibility evaluation of Au-NPs prepared from Zingiber officinale extract support its usage as vectors for the applications in drug delivery, gene delivery or as biosensors, where a direct contact with blood occurs.…”
Section: Introductionmentioning
confidence: 99%
“…Mukherjee and coworkers experimentally proved the nontoxic nature of these biogenic NPs in C57BL6/J female mice via various biochemical parameters along with a histopathology study of different organs. Even after successive injections of biogenic AuNPs (1 or 10 mg/kg/day) for seven days in healthy mice, no toxicity was observed (142). Moreover, it is interesting to note that in another study the same group reported that mice treated with chemically synthesized AuNPs showed broken alveolar walls with hyperplasic sinusoids as compared to the untreated or green synthesized AuNPs-treated mice (143).…”
Section: Toxicological and Immunological Aspectmentioning
confidence: 95%